STUDIES ON THE MATURITY AND FECUNDITY OF THE GANGETIC ANCHOVY, SETIPINNA PHASA (HAMILTON) - Jhingran, A G (Indian Journal of Fisheries, 2011)
RECORDINGS offish landings at Sadiapur Fish Assembly Centre, Allahabad, reveal that several species of clupeids represented by Setipinna phasa (Ham.), Gadusia chapra (Ham.), Gonialosa manminna (Ham.), juveniles of Hilsa ilisha (Ham.) and Corica soborna (Ham.) together constitute a moderately significant portion of the miscellaneous fishery. The miscellaneous group at Allahabad made up 18,360; 12,310 and 14,963 kg. respectively in the years 1958-1960 and contribution of S. phasa in these catches amounted to 588; 1,299 and 1,669 kg. This upward trend in the fishery of S. phasa at Allahabad, as evidenced from the landings, is quite significant and if maintained, the fishery may eventually assume a greater economic importance.